The enforcement of financial ombudsman scheme (FOS) to Malaysian takaful and insurance sectors: an analysis of alternative dispute resolution (ADR) from a period of 2013 to 2021 - Mohd. Zain, Nor Razinah; Mohd Noor, Azman; Wan Ismail, Wan Zamri; Awang, Hasila (2022)
The introduction of Islamic Financial Services Act 2013 or IFSA into Malaysian legislative landscape has shaped the Islamic financial services industry (IFSI) tremendously. Focusing on providing effective dispute settlement and financial protection towards the customers, IFSA creatively formulates the financial ombudsman scheme (FOS) which is effectively enforceable towards banking and insurance sectors. Without any exception, FOS is equivalently applicable towards Islamic banking and Takaful sectors in the country. Reaching towards FOS’s first decade of establishment, this research stands (i) to evaluate the application of FOS, specifically on the use of alternative dispute resolution in Takaful and insurance sectors from a period between 2013 to 2021. This is done by following the latest reports from the one and only Ombudsman for Financial Services (OFS) of Malaysia. This research also (ii) examines approaches of dispute settlement of selected cases which were taken by OFS. By appreciating the advantages of qualitative approaches, the researchers depend on doctrinal legal analysis, arm-chaired research strategies, and observational investigation from the identified trends in the IFSI. As a part of findings, it is found that there is a steady increase of cases which were referred to OFS. Types of complaints may be varied. During the period of COVID-19 lockdown which is between 2020 to 2021, there is an increase of complaints from the customers relating to scams. This is happened due to the change in the engagement and communication between the customers and their Takaful and insurance operators.